2017
DOI: 10.1111/exd.13473
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor blockade improves glucocorticoid‐induced skin atrophy but partially ameliorates anti‐inflammatory actions in an irritative model in human skin explants

Abstract: We recently demonstrated that blockade of the mineralocorticoid receptor (MR) effectively ameliorated GC-induced skin atrophy in healthy human skin explants and epidermal MR knockout mice. However, whether MR blockade improves the therapeutic index of glucocorticoids (GCs) in skin pathology was not investigated. We assessed the effects of GCs, MR antagonists (MRA) or both, in SDS-treated human skin explants. All treatments restored SDS-augmented epidermal thickness but only GC plus MRA restored the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
1
15
0
5
Order By: Relevance
“…There has also been interest in developing topical formulations of SP (Kelidari et al, 2015) to limit the systemic and potentially endocrine-disrupting effects of orally administered SP. Moreover, the topical use of SP and related mineralocorticoid receptor antagonists have been shown in clinical trials to counteract epidermal atrophy and the inhibition of wound healing caused by glucocorticoid treatment (Boix et al, 2018;Maubec et al, 2015;Nguyen et al, 2016). Chronic treatment with topical SP formulations, especially as proposed for use in damaged skin, would likely result in higher levels of SP than those associated with systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There has also been interest in developing topical formulations of SP (Kelidari et al, 2015) to limit the systemic and potentially endocrine-disrupting effects of orally administered SP. Moreover, the topical use of SP and related mineralocorticoid receptor antagonists have been shown in clinical trials to counteract epidermal atrophy and the inhibition of wound healing caused by glucocorticoid treatment (Boix et al, 2018;Maubec et al, 2015;Nguyen et al, 2016). Chronic treatment with topical SP formulations, especially as proposed for use in damaged skin, would likely result in higher levels of SP than those associated with systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…By using genetic and pharmacological approaches in mice and human skin explants, we and others demonstrated that blockade of the MR effectively improved GC-induced skin atrophy 5 , 16 , 18 . However, caution is advised for treating inflamed skin with GCs and MR inhibitors as their combined use decreased the anti-inflammatory actions of GCs in SDS-treated human skin explants 33 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings opened the attractive possibility of using combined therapy with GCs and pharmacological MR antagonists to improve GC-induced skin atrophy. However, in a model of contact dermatitis with human skin explants, MR blockade reduced GC-induced skin atrophy, but limited the repression of some inflammatory cytokines, suggesting that MR may be required for the full therapeutic response to GCs in this tissue [ 99 ]. This possibility is supported by the observations from our laboratory that mice lacking epidermal MR, similar to those lacking GR in this tissue, are more susceptible to skin inflammation [ 13 , 14 ].…”
Section: Gr and Mr In Adult Skin Homeostasismentioning
confidence: 99%